A Longitudinal Study of Preservice Teachers and their Efficacy Beliefs about Teaching and Learning Science - Petersen, Jacinta Elise (Curtin University, 2018)
This longitudinal study used a mixed methods design to investigate how, why and to what extent science teaching efficacy beliefs changed over time from preservice teacher education to first year teaching. Analysis of surveys and in-depth interviews showed that efficacy beliefs improved after science methods units and were sustained into the first year of teaching, despite varying experiences. Several key aspects have been identified that influence these efficacy beliefs at different stages of career development.